PEMANFAATAN DIGITAL MARKETING UNTUK PENGEMBANGAN BISNIS PADA KARANG TARUNA PERMATA ALAM PERMAI GEDANGAN SIDOARJO - Rudi Santoso; Achmad Yanu Alif Fianto; Novan Ardianto (Universitas Airlangga, 2020)
Nowadays, the development of social media and marketplaces as part of information technology contributes to business activities. This development has also changed the pattern and map of market competition to become much more competitive. Therefore, mastery of the use of social media and marketplaces is important and strategic that every business actor must have. However, this is in contrast to business people who are still pioneering or have just started their business, such as the youth at Karang Taruna Permata Alam Permai Gedangan Sidoarjo. With minimal knowledge and insight about social media and marketplaces it can hinder them from developing their start-up businesses. Therefore, this community service activity aims to increase the insight and knowledge of the Karang Taruna Permata Alam Permai Gedangan Sidoarjo in the use of social media and marketplaces to develop business. The methods used in the implementation of community service activities include training and mentoring related to increasing knowledge and insight. Knowledge and insight referred to in this activity is the use of information technology. This information technology can be used to develop a wider marketing reach. This activity has been going well and has an important contribution in improving the quality of the Permata Alam Permai Gedangan Sidoarjo Youth Organization which has been able to apply social media and marketplaces as part of the digital marketing tool. The use of this media can also encourage increased sales due to the development of exposure of the products being sold